The Impact of the Global Financial Crisis on Russia's Cooperation with the Countries of EurAsEC - Iskandar S. Kobersy; Tatiana I. Kuzmina; Anna I. Guseva; Nikita A. Lebedev; Tagira V. Ismagilova; Yulia S. Volkova (International Journal of Economics and Financial Issues, 2016)
The article considers the impact of the financial and economic crisis on Russia's cooperation with the EurAsEC countries. Because crises are an integral part of any economic system, a deep analysis should be carried out. We consider the integration at the micro level and prospects of Russia's cooperation with the EurAsEC, the prospects for cooperation between Russia and the EurAsEC countries should be assessed in different ways. Speaking about the cooperation it should be noted that the main weakness of the countries dependent on the prices of natural resources, which are the main export of all countries, including Russia. After all, the raw material orientation determines the country's place in the world. And so the main task here is to develop the production of finished products and the development of knowledge-based industries.